Ankk1 Loss of Function Disrupts Dopaminergic Pathways in Zebrafish - Leggieri, Adele; García-González, Judit; Torres-Perez, Jose V.; Havelange, William; Hosseinian, Saeedeh; Mech, Aleksandra M.; Keatinge, Marcus; Busch-Nentwich, Elisabeth M.; Brennan, Caroline H. (Frontiers in Neuroscience, 2022)
ANKK1 is a member of the receptor-interacting protein serine/threonine kinase family, known to be involved in cell proliferation, differentiation and activation of transcription factors. Genetic variation within the ANKK1 locus is suggested to play a role in vulnerability to addictions. However, ANKK1 mechanism of action is still poorly understood. It has been suggested that ANKK1 may affect the development and/or functioning of dopaminergic pathways. To test this hypothesis, we generated a CRISPR-Cas9 loss of function ankk1 zebrafish line causing a 27 bp insertion that disrupts the ankk1 sequence introducing an early stop codon. We found that ankk1 transcript levels were significantly lower in ankk1 mutant (ankk127ins) fish compared to their wild type (ankk1+/+) siblings. In ankk1+/+ adult zebrafish brain, ankk1 protein was detected in isocortex, hippocampus, basolateral amygdala, mesencephalon, and cerebellum, resembling the mammalian distribution pattern. In contrast, ankk1 protein was reduced in the brain of ankk127ins/27ins fish. Quantitative polymerase chain reaction analysis revealed an increase in expression of drd2b mRNA in ankk127ins at both larval and adult stages. In ankk1+/+ adult zebrafish brain, drd2 protein was detected in cerebral cortex, cerebellum, hippocampus, and caudate homologue regions, resembling the pattern in humans. In contrast, drd2 expression was reduced in cortical regions of ankk127ins/27ins being predominantly found in the hindbrain. No differences in the number of cell bodies or axonal projections detected by anti-tyrosine hydroxylase immunostaining on 3 days post fertilization (dpf) larvae were found. Behavioral analysis revealed altered sensitivity to effects of both amisulpride and apomorphine on locomotion and startle habituation, consistent with a broad loss of both pre and post synaptic receptors. Ankk127ins mutants showed reduced sensitivity to the effect of the selective dopamine receptor antagonist amisulpride on locomotor responses to acoustic startle and were differentially sensitive to the effects of the non-selective dopamine agonist apomorphine on both locomotion and habituation. Taken together, our findings strengthen the hypothesis of a functional relationship between ANKK1 and DRD2, supporting a role for ANKK1 in the maintenance and/or functioning of dopaminergic pathways. Further work is needed to disentangle ANKK1’s role at different developmental stages.